Center of Pressure in Relation to Foot Morphology and Knee Symptoms in Older Women With Medial Knee Joint Deformity: A Cross-Sectional Study - Nakazato, Kaede; Pataky, Todd; Taniguchi, Masashi; Saeki, Junya; Yagi, Masahide; Motomura, Yoshiki; Okada, Shogo; Okada, Sayaka; Fukumoto, Yoshihiro; Kobayashi, Masashi; Kanemitsu, Kyoseki; Ichihashi, Noriaki (Archives of physical medicine and rehabilitation, 2025)
•To reveal correlations between center of pressure (COP) trajectory, foot morphology, and knee symptoms.•Higher navicular/foot ratio was correlated with a lateral shift of COP in single stance phase.•Lateral shift of COP in loading response phase was correlated with knee symptoms severity. To examine the correlations amongst center of pressure (COP) trajectories, foot morphology, and knee symptoms in older women with medial knee deformity. This was a cross-sectional study. Participants were recruited from 2 local orthopedic clinics. Female patients with medial knee deformity (Kellgren–Lawrence grade ≥1) aged 60 years or older (N=84). Not applicable. COP trajectories during comfortable gait were obtained using a plantar pressure distribution platform. As foot morphology metrics, hallux valgus angle, navicular/foot ratio, and leg-heel alignment were measured. The knee society scoring system was used to evaluate knee symptom severity. We used statistical parametric mapping for COP trajectory analysis to reduce the bias caused by data extraction. Multiple linear regression in statistical parametric mapping was used to determine the correlations amongst foot morphology, knee symptom severity, and COP trajectories. There was a correlation between higher navicular/foot ratio and medial shift on COP at initial contact (0%∼3.0% stance phase, P<.05) and at toe-off (95.3%∼100% stance phase, P=.04). Also, higher navicular/foot ratio was associated with lateral shift of COP during single leg stance phase (8.3%∼80.1% stance phase, P<.01). We also found a significant correlation between lateral shift of COP during loading response phase (6.8%∼19.0% stance phase) and knee symptom severity (P=.03). Our results indicated that patients with severe knee symptoms may benefit from intervention to modify the foot arch and to medially shift the COP, which may be capable of relieving knee symptoms. Although our results do not directly show pain reduction, a medial COP shift could indeed reduce pain in cases where knee adduction moment is responsible for pain. These findings may contribute to the further development of conservative intervention, which focus on foot morphology of patients with knee osteoarthritis.